2010
DOI: 10.1177/1069397110366670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Teacher Acceptance, Self-Concept, and School Attitude on the Academic Achievement of School-Age Children in Turkey

Abstract: This study investigated the influence of perceived teacher acceptance, children’s self-concept, and children’s attitude toward school on children’s academic achievement. The sample included 223 fifth-grade students in Istanbul, Turkey. The Teacher Acceptance-Rejection/Control Questionnaire, Piers-Harris Self-Concept Scale, and School Attitude Assessment Survey-Revised were utilized in data collection. Achievement was assessed by grade point average (GPA). Results showed that the perception of teacher acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
2
18
0
2
Order By: Relevance
“…In contrast, meta-analyses of performance on standardized tests have reported gender differences in favor of males in mathematics (e.g., Else-Quest et al, 2010;Hyde et al, 1990; but see Lindberg et al, 2010) and science achievement (Hedges & Nowell, 1995), whereas they have shown a female advantage in reading comprehension (e.g.. Hedges & Nowell, 1995). This contrast in findings makes it clear that the generalized nature of the female advantage in school marks contradicts the popular stereotypes that females excel in language whereas males excel in math and science (e.g., Halpem, Straight, & Stephenson, 2011).…”
Section: Overall Results: Implicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, meta-analyses of performance on standardized tests have reported gender differences in favor of males in mathematics (e.g., Else-Quest et al, 2010;Hyde et al, 1990; but see Lindberg et al, 2010) and science achievement (Hedges & Nowell, 1995), whereas they have shown a female advantage in reading comprehension (e.g.. Hedges & Nowell, 1995). This contrast in findings makes it clear that the generalized nature of the female advantage in school marks contradicts the popular stereotypes that females excel in language whereas males excel in math and science (e.g., Halpem, Straight, & Stephenson, 2011).…”
Section: Overall Results: Implicationsmentioning
confidence: 88%
“…Potential national differences in the magnitude of gender differences in school achievement as well as in test achievement have been examined extensively (Else-Quest et al, 2010). Thus, it is only fitting that this variable should be considered here.…”
Section: National Originmentioning
confidence: 99%
“…Okula karşı tutum okul tükenmişliğinin anlamlı bir yordayıcısıdır (Seçer, 2015), H7. Okula karşı tutum akademik başarının anlamlı bir yordayıcısıdır (Berberoğlu ve Balcı, 1994;Cheng ve Chan, 2003;Erkman, Caner, Sart, Börkan ve Şahan, 2010;Ford ve Harris, 1996;McCoach ve Siegle, 2003), H8.Okula yabancılaşma okul tükenmişliğinin anlamlı bir yordayıcısıdır (Huang ve Lin, 2010;Jia, Rowlinson, Kvan, Lingard ve Yip, 2009), H9.Okula yabancılaşma akademik başarının anlamlı bir yordayıcısıdır (Kocayörük, 2007;Roeser vd., 1994), H10.Okul tükenmişliği akademik başarının anlamlı bir yordayıcısıdır (Balkıs, Duru, Buluş ve Duru, 2011;Çapulcuoğlu ve Gündüz, 2013;Kutsal, 2009;Schaufeli vd., 2002).…”
Section: Araştırmanın Hipotezleriunclassified
“…Erkman et al [38] examined the influence of perceived teacher acceptance on academic achievement of school age children in Turkey. The findings indicated a significant correlation between perceived teacher acceptance and academic achievement of boys (r = 0.27, p <0.05).…”
Section: Teacher Perception and Support And Academic Achievementmentioning
confidence: 99%